2016
DOI: 10.1007/s12072-016-9751-4
|View full text |Cite
|
Sign up to set email alerts
|

Prednisolone plus S-adenosil-l-methionine in severe alcoholic hepatitis

Abstract: Management of severe alcoholic hepatitis with prednisolone plus SAMe was associated with better therapy response (p = 0.044) and less frequent HRS occurrence (p = 0.035). Mortality was not significantly lower in the prednisolone-SAMe group than in the prednisolone-only group at 28 days (10 vs. 0 %, p = 0.151).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 16 publications
0
17
0
5
Order By: Relevance
“…In this regard, administration of an antioxidant cocktail, including vitamin E and NAC, along with nutritional supplements, to patients with AH failed to improve survival in this cohort, whereas Stewart et al, using a similar approach, reported increased short‐term outcome . Interestingly, however, the replenishment of hepatic GSH levels with either NAC or S‐adenosyl‐methionine (SAM) has been shown to increase the efficacy of prednisolone in patients with advanced ALD . Although SAM acts as a GSH precursor, it is a methyl donor and therefore regulates multiple targets in hepatocytes .…”
Section: Antioxidants Therapy: Critical Mitochondrial Antioxidants Bamentioning
confidence: 80%
“…In this regard, administration of an antioxidant cocktail, including vitamin E and NAC, along with nutritional supplements, to patients with AH failed to improve survival in this cohort, whereas Stewart et al, using a similar approach, reported increased short‐term outcome . Interestingly, however, the replenishment of hepatic GSH levels with either NAC or S‐adenosyl‐methionine (SAM) has been shown to increase the efficacy of prednisolone in patients with advanced ALD . Although SAM acts as a GSH precursor, it is a methyl donor and therefore regulates multiple targets in hepatocytes .…”
Section: Antioxidants Therapy: Critical Mitochondrial Antioxidants Bamentioning
confidence: 80%
“…Furthermore, the formation of PC is reduced in various chronic liver diseases including intrahepatic cholestasis, cholestasis of pregnancy, and alcoholic liver disease (149)(150)(151). There have been few randomized controlled trials to assess the efficacy of SAMe in chronic liver diseases (152,153), but in studies conducted thus far, SAMe treatment improved pruritus.…”
Section: Perspectivesmentioning
confidence: 99%
“…Although not statistically significant, the six-month survival rate is 90% in the prednisolone plus SAMe group vs 75% in the prednisolone group. Larger trials are needed to validate the study results[187]. …”
Section: New Therapeutic Optionsmentioning
confidence: 99%